Experimental study on the permeability variation of sandstone at cyclic stress: Implication for underground gas storage. (April 2023) - Zhou, Junping; Deng, Guangrong; Tian, Shifeng; Xian, Xuefu; Yang, Kang; Zhang, Chengpeng; Dong, Zhiqiang
Abstract: Underground gas storage (UGS) of CH4 and H2 is an economical and reliable solution for large-scale energy storage. Cyclic gas injection-withdrawal of UGS can induce periodical stress perturbation in reservoirs, which may significantly influence the permeability of the reservoir. Understanding the effect of cyclic stress on the permeability evolution in reservoirs is important for optimizing the injection-withdrawal strategy. Therefore, the alterations of rock mechanical properties, permeability and its stress sensitivity of a sandstone sample from UGS under cyclic stress were obtained by experiments. Results indicated that the stress-strain curves of the sandstone under cyclic stress was not coincided and formed a hysteresis loop, and with the increasing cycles, the hysteresis loop transformed from sparse to dense. With the increase of cycles, the elastic modulus ( E ) in the sandstone first increased, then decreased slightly, and finally almost remained constant, while the Poisson's ratio ( v ) increased at early cycles and then nearly remain unchanged. The evolution of permeability of sandstone can be separated into three stages: rapid decline stage (1-10th cycles), slight decline stage (10-30th cycles), and almost stable and unchanged stage (30-50th cycles), which shows good consistent with the deformation behaviors of sandstone. Correspondingly, the change of compressibility coefficient in the sandstone can also be divided into three stages, including the rapid decline stage (1-10th cycles), slight increase stage (10-30th cycles) and slow decline stage (30-50th cycles), which shows an opposite variation trend with the rock mechanical properties in sandstone. For a certain cyclic stress loading-unloading, the permeability and compression coefficient in the sandstone at minimum stress were larger than those at maximum stress. The irreversible permeability loss rate of the sandstone showed good consistent with the changes of stress sensitivity coefficient caused by cyclic stress. Highlights: The effect of cyclic stresses on rock mechanical properties and permeability was studied. Cyclic stresses induced the elastic modulus and Poisson's ratio increase in sandstone. The permeability of sandstone was decreased with the stress cycle numbers. The stress sensitivity of permeability in sandstone decreased with the increasing cycles. The stress sensitivity of permeability and mechanical properties showed a good correlation.